Elevated levels of gut microbiota dependent trimethylamine N-oxide: An indicator of cardiovascular disease. (June 2021) - Caroff, Charlotte
Abstract: Cardiovascular disease (CVD) remains the leading cause of death globally, responsible for an estimated 17.9 million deaths annually. Traditional screening and diagnostic tests often fail to identify those at risk until a late stage, it is therefore essential to develop new predictive tests to enable diagnosis at an earlier stage to facilitate preventative treatments. Recently, many studies have shown that high levels of circulating Trimethylamine N-oxide (TMAO) are indicative of an increased risk of CVD. Through the analysis of TMAO levels it was found patients whose TMAO level was in the 4th quartile had a 2.29 fold increase of major adverse cardiac events (MACE) over patients whose level was in the 1st quartile (p < 0.05). These studies have also demonstrated the role of the gut microbiome in the formation of TMAO. This review will provide an overview of the role of the gut microbiome and explore the evidence linking TMAO and CVD.